How Urban Food Pantries are Stocked and Food Is Distributed: Food Pantry Manager Perspectives from Baltimore. Issue 4 (3rd July 2020) - Yan, Sally; Caspi, Caitlin; Trude, Angela C. B.; Gunen, Bengucan; Gittelsohn, Joel
ABSTRACT: Low-income, food-insecure Baltimore residents frequently rely on food pantries. In this study, pantry managers were key informants who shared information on how and why certain products were obtained and distributed and their perceptions around the need for nutritious products. Managers prioritized providing "staple" foods that could comprise a meal, and most of these foods were shelf-stable. Most pantries distributed pre-assembled, uniform bags, rather than using a client choice method. Managers did not perceive that their clients wanted healthy foods, despite clients informing them of diet-related health conditions. Manager-level training may be necessary to align pantry operations with clients' food needs.